A Gate in the Wall of Sound: Embodiment and traditional gatekeeping in music photography. (7th February 2019) - Lough, Kyser
Abstract : This study examines how gatekeeping aspects of photography, particularly embodied gatekeeping, interact with a subset of photojournalism that faces numerous barriers to access—music photography. Through in-depth interviews with concert photographers in a large metropolitan city, this study expands upon what is known about gatekeeping when it comes to visual media. While much has been studied on photojournalists as a whole, little is known about particular subgroups, such as music photographers. As a part of lifestyle journalism, concert photography contributes to the interaction of popular culture and society, showing us visual evidence of the spectacle of musical performance. Gatekeeping practices are found not only in the managers who issue credentials for access and control where photographers can shoot from but also in the community of photographers themselves. This is extended into embodied gatekeeping in how they jostle for access to space in the pit and enforce the rules with their bodies, such as physically pushing a camera out of the way.